2003
DOI: 10.34194/geusb.v1.4644
|View full text |Cite
|
Sign up to set email alerts
|

The Jurassic of Denmark and Greenland: key elements in the reconstruction of the North Atlantic Jurassic rift system

Abstract: The Jurassic succession of Denmark is largely confined to the subsurface with the exception of exposures on the island of Bornholm in the Baltic Sea. In East Greenland, in contrast, the Jurassic is extensively exposed. Comparison of basin evolution in the two regions, which now occur on two separate plates, thus relies on highly different datasets. It is possible nevertheless to construct an integrated picture allowing testing of hypotheses concerning basin evolution, regional uplift, onset and climax of rifti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…The change in provenance appears to coincide with a major switch in drainage, from a predominantly northerly dispersal system to one directed to the south. It seems likely that this was an early expression of the Mid Jurassic tectonism and uplift, which resulted in the widespread omission of the Early Jurassic across East Greenland (Surlyk & Ineson, ). The changing stress fields related to this event appears to also be recorded in the realignment of active faulting from predominantly NE–SW during the Triassic (Andrews & Decou, ; Guarnieri et al, ) to largely N–S during the Jurassic (Price & Whitham, ).…”
Section: Discussionmentioning
confidence: 99%
“…The change in provenance appears to coincide with a major switch in drainage, from a predominantly northerly dispersal system to one directed to the south. It seems likely that this was an early expression of the Mid Jurassic tectonism and uplift, which resulted in the widespread omission of the Early Jurassic across East Greenland (Surlyk & Ineson, ). The changing stress fields related to this event appears to also be recorded in the realignment of active faulting from predominantly NE–SW during the Triassic (Andrews & Decou, ; Guarnieri et al, ) to largely N–S during the Jurassic (Price & Whitham, ).…”
Section: Discussionmentioning
confidence: 99%
“…The most important phase of extensional tectonics since the Carboniferous -early Permian, culminated in middle Volgian times (Tithonian-Berriasian transition around 145 Ma; Surlyk & Ineson 2003), at the Jurassic-Cretaceous boundary (Surlyk 1978b(Surlyk , 2003Surlyk & Korstgård 2013). The area north of Kong Oscar Fjord broke up into tilted blocks, which became progressively fragmented and narrower with time, and deposition was almost exclusively coarse grained.…”
Section: Wwwgeusbulletinorgmentioning
confidence: 99%
“…We will refer to these two faults as the post-Devonian Main Fault system. Important phases of rifting took place during the early and late Carboniferous, late Permian, late Jurassic and Cretaceous, prior to the opening of the North-East Atlantic at the Paleocene-Eocene transition (Surlyk 1990(Surlyk , 2003Stemmerik et al 1993;Stemmerik 2000;Surlyk & Ineson 2003). Parsons et al (2017) studied the geology of Traill Ø and Geographical Society Ø and identified three main rift phases during the Devonian-Triassic, Jurassic-Cretaceous and Palaeogene.…”
Section: Wwwgeusbulletinorgmentioning
confidence: 99%
“…A peneplain covered by Middle and Upper Jurassic sandstones of marine origin is exposed on Kuhn Ø and Milne Land (Surlyk 2003;Surlyk & Ineson 2003). Extensive denudation that started in the early Jurassic most likely led to the formation of this surface.…”
Section: Large-scale Landscapesmentioning
confidence: 99%